Respon Fisiologi Kedelai (Glycine max. L (Merr)) Varietas Ajasmoro Di Kecamatan Ruteng, Kabupaten Manggarai - Devi Liana; Tri Astuti; Dumaris Priskila Purba; Fanny Juliarti Panjaitan (Fakultas Pertanian, Universitas Timor, 2023)
Soybean plants require high light intensity so that if there is a decrease in solar radiation for a long time it will affect the soybeans growth and development. This study aims to determine the soybeans physiological respons to rice straw compost application in the highlands. This research was carried out for 4 months from March to July 2022 in Ruteng District, Manggarai Regency. This experiment used a non-factorial randomized block design (RBD) consisting of four treatment levels, namely control, 240 g/polybag rice straw compost, 480 g/polybag rice straw compost and 720 g/polybag rice straw compost. The results showed that the highest plant N uptake was obtained at the dose of rice straw compost 240 g/polybag. The rice straw compost application to the variable plant height and chlorophyll content was not significantly different. This is a form of soybeans adaptation mechanism in the highlands.